Pengaruh Kawasan Malioboro Sebagai Area Pedestrian Terhadap Minat Kunjungan Wisatawan - Lilik Edi Saputro; Nining Yuniati; Tutut Herawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Malioboro is one of the popular tourist destinations in the city of Yogyakarta, and also as a tourism icon in the city of Yogyakarta which is often visited by tourists. Malioboro is also a link between the monument and the palace or better known as the imaginary line that cannot be separated from the concept of the Yogyakarta Palace's urban planning philosophy. Pedestrian Malioboro is located in the tourist area of Malioboro with high economic, social and cultural values, making it a favorite destination for tourists. The method used in this study uses quantitative methods. The quantitative method in this study was used to analyze the influence of the Malioboro area as a pedestrian area on the interest of tourist visits. Interest in visiting is basically a feeling of wanting to visit an interesting place to visit. Interest in visiting is the act of tourists in choosing or deciding to visit a tourist attraction based on their experience in traveling.